Inquiry as a context-based practice – a case study of pre-service teachers' beliefs and implementation of inquiry in context-based science teaching. Issue 14 (22nd September 2019) - Herranen, Jaana; Kousa, Päivi; Fooladi, Erik; Aksela, Maija
ABSTRACT: The aim of this study is to provide an understanding of context-based inquiry teaching within a humanistic perspective on science education by studying pre-service teachers' beliefs about inquiry and their implementations of inquiry in their context-based teaching sequences. Therefore, five pre-service teachers enrolled in a university undergraduate course called 'Inquiry-based chemistry education II' (5 ECTS) were involved in an empirical case study. The pre-service teachers' implementations of inquiry were studied from their reports on self-designed context-based inquiry teaching sequences for students age 13–15, and their beliefs by interviewing them after the course. The results indicate that the most frequent aspects of inquiry, which were implemented, were that inquiry (i) includes a context, (ii) is a way to act, (iii) is a way to think, and (iv) includes source/information evaluation and argumentation. The pre-service teachers' beliefs about inquiry were shown to reflect manifold aspects of inquiry, such as the difficulty in explaining it. However, this difficulty in encapsulating inquiry into a clear-cut definition is not necessarily an impediment to inquiry-based teaching. Furthermore, inquiry is inherently context-bound, and context-based teaching requires extra-situational knowledge from the context and not only declarative knowledge from science. This should be considered to support effective professional development.